2006
DOI: 10.1111/j.1365-2400.2006.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among condition indices, feeding and growth of walleye in Lake Erie

Abstract: Condition indices are often used as surrogates of fish health, growth, and feeding and to compare ecological well-being among fish populations. In an effort to identify easily measured indices, growth and food consumption were compared with gonadal-somatic index, liver-somatic index (LSI), fat-somatic index and relative weight (W r ) for ages 1-3 walleye, Sander vitreus (Mitchill), in Lake Erie from 1986 to 1988. The LSI and W r were significantly correlated with growth rate or food consumption, but correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Higher Hg concentrations in the spring were likely attributable to changes in fish body condition, which has been shown to improve from spring to fall in Lake Erie walleye (Hartman and Margraf 2006), and is negatively correlated to fish-Hg concentration (Sun and Hitchin 1990; Greenfield et al 2001;Dittman and Driscoll 2009). Interaction terms were within one standard error of zero (not shown) and, therefore, did not significantly affect the modeled predictions.…”
Section: Output Summarymentioning
confidence: 81%
“…Higher Hg concentrations in the spring were likely attributable to changes in fish body condition, which has been shown to improve from spring to fall in Lake Erie walleye (Hartman and Margraf 2006), and is negatively correlated to fish-Hg concentration (Sun and Hitchin 1990; Greenfield et al 2001;Dittman and Driscoll 2009). Interaction terms were within one standard error of zero (not shown) and, therefore, did not significantly affect the modeled predictions.…”
Section: Output Summarymentioning
confidence: 81%
“…For example, it has become commonplace to assess fish nutritional health using direct measures of energy reserves such as total lipid content and/or concentrations of fatty acids (Morton and Routledge 2006;Peters et al, 2007;Cai et al, 2007;Arts and Kohler 2009), used alone or in combination with other fish health indicators, such as condition indices and indicators of disease and infection such as hematological and blood protein measures (Lloret et al, 2002;Adams et al, 2003;Hartman and Margraf 2006;Islam and Tanaka 2006;DeBruyne et al, 2008;Butterworth et al, 2008). These measures become increasingly valuable when they reliably inform managers to take preventative actions to avoid overexploitation or other anthropogenic stresses on economically valuable fish stocks.…”
Section: Introductionmentioning
confidence: 99%
“…However, monitoring carried out in 2004 (unpublished data) did not indicate any disturbance of the age-structure of the population, which was seen to be made up of a relatively high percentage of younger individuals: more than 53% of the population was accounted for by specimens less than 16 cm long-a size which perch in Lake Piediluco reach by the age of two years. The worsening of the environmental condition of the lake due to the change in the trophic state (Mearelli, 1988) and increasing competition with some allochthonous species recently introduced into the lake Trusso et al, 2006) probably play the greatest role in determining the change observed in the growth rate of the population: decreased growth rates and increased age at maturity suggest that prey levels are becoming inadequate to sustain perch production at existing levels (Hartman & Margraf, 2006). Food availability and population density affect the growth rate of perch (Shafy & Maitland, 1971;Paukert & Willis, 2001): low perch density is probably the most important determinant of this change in growth (Houthuijzen et al, 1993;Dörner et al, 2003).…”
Section: Discussionmentioning
confidence: 97%